Metal Casting Furnace Design Development Using Computer Simulation - Irianto, Ramadhan Wahyu; Pradana, Yanuar R.A.; Suprayitno, Suprayitno (Universitas Negeri Malang, 2024)
Metal foundries still rely heavily on crucible furnaces. The current furnace design, which is currently being used by the partner industry, has been found to be not properly designed and will result in a reduction in efficiency. CFD simulation will be used to find the optimal melting furnace design. This research simulation consists of 3 stages: pre-processing, solving, and post-processing. There are two furnace geometries, cylindrical and hexagonal, while the burner location will be divided into 3 positions, namely P1, P2, and P3. The most optimal furnace design will be used as a basis for the verification testing process. The process of comparing the old and the new smelting furnace design is carried out to understand the performance and characteristics of each furnace. The simulation results for the average crucible temperature in the cylindrical furnace were obtained as follows: 288.5 ºC for the P1 burner, 306.2 ºC for the P2 burner, and 284.5 ºC for the P3 burner. Meanwhile, the simulation results show that the average crucible temperature value in the hexagonal furnace is 290.0 ºC for the P1 burner, 281.6 ºC for the P2 burner, and 237.8 ºC for the P3 burner. The verification testing process produced an average crucible temperature value of 237.5 ºC. Furthermore, the comparison test from the old and new furnace designs to melt 2.5 kg of aluminium at 680 ºC with the old furnace took approximately 30 minutes and 33 minutes with the new furnace. The new furnace produced much more uniform melting than the old furnace.